STUDY INDUSTRIAL LIQUID WASTE POLLUTION USING GEOELECTRIC METHOD IN SUKAREGANG, GARUT REGENCY - Nurul Fauziah, Sasqia
Clean water is one of the primary human needs. The current rapid pace of the industrial sector causes more and more industrial waste to be produced which can contaminate clean water. Sukaregang is a leather tanning industry area. Industrial areas, either directly or indirectly, produce waste that can disrupt environmental stability and the availability of clean water. Limited facilities for processing and utilizing industrial waste in this area result in reduced waste treatment optimally, so that the untreated waste can seep and contaminate the surrounding area. The process of seepage of sewage occurs below the surface of the soil so it is difficult to observe. The identification of waste seepage below the ground surface is carried out using the Wenner configuration type resistance geoelectric method, soil magnetic grains and using the method of measuring water samples in situ. Resistivity data collection was carried out around the Ciwalen Garut river in West Java as many as 3 lines with a distance between the lines of 5 meters and using 16 electrodes. Data processing is carried out using Res2dinv software and data interpretation is based on resistivity tables of rocks, minerals and chemicals. The interim results obtained based on the geoelectric method found the presence of seepage of wastewater infiltrating on 3 lines. Resistivity values based on measurement results vary from 0,1 to 181,9 ?m. The value is associated with clay rocks of different densities. Allegedly polluted areas on the three lines are at the measurement point of ±10 to ±20 meters with a depth of about 0 – 10 meters. The low value of subsurface resistivity on all three lines is estimated to be polluted by seepage of liquid waste that has low resistivity. Based on the analysis of soil samples using SEM-EDS, there are soil grains in the form of octahedral and sherule indicating that the soil is the result of weathering of igneous rock in a volcanic area where some of the soil is suspected to be due to the influence of anthropogenic sources. The grain composition based on EDS also shows a chromium (Cr) content that exceeds the quality standard, indicating seepage of tannery waste into the area around the Ciwalen river. Analysis of surface water samples also showed that the conductivity, TDS, and pH values were highest in the area closest to the river and decreased to the sample points that were farthest from the river.